Penerapan Manajemen Risiko Pembiayaan Murabahah di BPRS Mitra Mentari Sejahtera Ponorogo - Ary Eka Muthiara Sary; Irma Yuliani (Jurnal Inovasi Ekonomi Syariah dan Akuntansi, 2025)
Murabaha financing is one of the leading products at PT. BPRS Mitra Mentari Sejahtera Ponorogo, especially for consumptive and productive financing. Therefore, the application of risk management and mitigation is very important to minimize financing risks. This study aims to determine how risk management and mitigation are applied to murabaha financing at BPRS. The method used is descriptive qualitative with field research and data collection techniques in the form of interviews and documentation. The results of this study indicate that risk management has been implemented at PT. BPRS Mitra Mentari Sejahtera Ponorogo, emphasizing the stages of identifying and measuring risk through 5C+1S analysis (character, capacity, capital, condition of economy, collateral, and sharia), although it only focuses on the aspects of capacity and collateral as well as BI checking. The risk mitigation process is also carried out through insurance and the use of collateral, especially gold pawn. Although it has a positive impact, its implementation is not yet optimal, as indicated by the high level of problematic financing and an increase in NPF.